Intermolecular Interactions in Fluorinated Tetraarylporphyrins: An Experimental and Theoretical Study. Issue 16 (2nd May 2014) - Soman, Rahul; Sujatha, Subramaniam; De, Susmita; Rojisha, Vallyanga Chalil; Parameswaran, Pattiyil; Varghese, Babu; Arunkumar, Chellaiah
Abstract: Crystallographic studies of the fluorinated tetraarylporphyrin 5, 10, 15, 20‐tetrakis(2′, 3′, 5′, 6′‐tetrafluoro‐ N, N ‐dimethyl‐4‐anilinyl)porphyrin and its metal complexes [MTF4 DMAP; M = 2H· 2H2 O, 1 ; Ni II · THF, 2 ; Cu II · 5H2 O, 3 ; and Zn II · (THF)2, 4 ; THF = tetrahydrofuran] are reported. To analyse the weak intermolecular interactions, we have used a combination of energy decomposition analysis and Hirshfeld surface analysis, which allowed us to elucidate the nature of various close contacts. The energy decomposition analysis shows that dispersive interactions involving fluorine atoms significantly contribute to the stabilizing intermolecular interactions. Cooperative weak interactions such as C–F··· H/C/F, C–H··· π and H··· H are responsible for the formation and stabilization of the supramolecular self assemblies. Abstract : Hirshfeld surface and energy decomposition analyses of metalloporphyrins show that dispersive interactions involving fluorine atoms are the major contributors to the molecular crystal packing.